Clinical Features and Short-term Outcomes of 102 Patients with Corona Virus Disease 2019 in Wuhan, China - Cao, Jianlei (Clin Infect Dis, 2020)
OBJECTIVE: In December, 2019, a series of pneumonia cases of unknown cause emerged in Wuhan, Hubei, China. In this study, we investigate clinical and laboratory features and short-term outcomes of patients with Corona Virus Disease 2019(COVID-19). METHODS: All patients with COVID-19 admitted to Wuhan University Zhongnan Hospital in Wuhan, China, between January 3 and February 1, 2020 were included. All those patients were with laboratory-confirmed infection. Epidemiological, clinical, radiological characteristics, underlying diseases, laboratory tests treatment, complications and outcomes data were collected. Outcomes were followed up at discharge until Feb 15, 2020. RESULTS: The study cohort included 102 adult patients. The median (IQR) age was 54 years (37-67years) and 48.0% were female. A total of 34 patients (33.3%) were exposed to source of transmission in the hospital setting (as health care workers, patients, or visitors) and 10 patients (9.8%) had a familial cluster. Eighteen patients (17.6%) were admitted to the ICU, and 17 patients died (mortality, 16.7%; 95% confidence interval [CI], 9.4%-23.9%). Among patients who survived, they were younger, more likely were health care workers and less likely suffered from comorbidities. They were also less likely suffered from complications. There was no difference in drug treatment rates between the survival and non-survival groups. Patients who survived less likely required admission to the intensive care unit (14.1% vs. 35.3%). Chest imaging examination showed that death patients more likely had ground-glass opacity (41.2% vs. 12.9%). CONCLUSIONS: The mortality rate was high among the COVID-19 patients described in our cohort who met our criteria for inclusion in this analysis. Patient characteristics seen more frequently in those who died were development of systemic complications following onset of the illness and the severity of disease requiring admission to the ICU. Our data support those described by others that COVID-19 infection results from human-to-human transmission, including familial clustering of cases, and nosocomial transmission. There were no differences in mortality among those who did or did not receive antimicrobial or glucocorticoid drug treatment.